Pelaksanaan Pembinaan Kelompok Sadar Wisata Pada Dinas Pariwisata Kabupaten Pasuruan (Studi di Tiga (3) Desa Wisata): Implementation Of Tourism Aware Group Development at The Pasuruan District Tourism Office (Study At Three (3) Tourism Villages) - Zuliatin, Mafadhotul; Parmono, Budi; Hidayati, Rahmatul (Universitas Medan Area, 2025)
This study aims to analyze the implementation of capacity-building programs for Tourism Awareness Groups (Pokdarwis) in Pasuruan Regency, with a case study focusing on three tourism villages: Cendono, Wonokitri, and Gerbo. It also seeks to identify the challenges encountered during the development process and to formulate alternative strategies to address these obstacles. The research employs a juridical-empirical approach, integrating both legislative analysis and a sociological perspective. The findings indicate that the Department of Tourism of Pasuruan Regency conducted 12 types of training programs for Pokdarwis members between January 2022 and August 2023, in accordance with Article 30 of Law No. 10 of 2009 on Tourism. The main obstacles identified include the low level of member participation in training activities, mismatched budget allocations relative to the actual needs of the Pokdarwis, and the absence of post-training follow-up programs. To overcome these challenges, the Tourism Office implemented direct educational outreach to Pokdarwis members and reallocated additional funding through the mechanism of Regional House of Representatives’ (DPRD) Special Budget Proposals (Pokok-Pokok Pikiran or Pokir).